A culture of open reporting results in improved quality of bladder tumour resections: a closed loop audit. (September 2016) - Ching, Daniel; Anastasiadis, Eleni; Patel, Pareeta; Sahu, Mahua; Sandhu, Sarb
Objective: Bladder cancer is the commonest cancer of the urinary tract. Transurethral Resection of Bladder Tumour (TURBT) is the gold standard for diagnosis and treatment of non-muscle invasive bladder cancer. The absence of muscle in a TURBT specimen is associated with a significantly higher risk of residual disease, early recurrence and tumour under staging. Materials and methods: TURBT and bladder biopsy specimens were examined before and after the introduction of an open reporting system as a quality improvement exercise. All specimens from the 4th quarter (between 2010 and 2014) were examined to determine the effect of open reporting on our inadequate resection rates. Results: A total of 244 cases were performed under the care of 5 consultant urologists. Analysis revealed a significant improvement in quality of both T1 and Ta resections (p=0.04*; p=0.02*) after the introduction of open reporting. The total number of TURBT cases increased per year, however the percentage of inadequate resections has significantly decreased (p=0.02*). Conclusion: Individual reporting provided surgeons with direct, personal and timely feedback on their performance. It did not negatively impact on trainee participation, but led to improved training outcomes. We have demonstrated that our simple intervention has improved quality of patient care.